Philippine Indios were European constitutional Spaniards Filipino reception of the Cádiz constitution - Perez, Abisai (Philippine studies : historical and ethnographic viewpoints)
"This article traces the impact of the 1812 Cádiz Constitution on the native population of the Philippines. It analyzes the contradictions that the constitution posed to the juridical status of natives who were granted citizenship rights and explores how the natives recieved the charter through the constitutional oath, a civic festival whereby local subjects swore fealty to the charter. It analyzes the Spanish legal culture that sustained the special legal régime granted to natives since the late sixteenth century, the debates that originated in the Cortes de Cádiz, and the modified version of the constitution that was created to dovetail with local realities."